Mitochondrial Gene Diversity and Host Specificity of Isospora in Passerine Birds - Kubiski, Steven V.; Witte, Carmel; Burchell, Jennifer A.; Conradson, Dylan; Zmuda, Alexandra; Barbon, Alberto Rodriguez; Vilches-Moure, Jose G.; Felt, Stephen A.; Rideout, Bruce A. (Frontiers in Veterinary Science, 2022)
Isospora infections are common in both wild and captive passerine species. Many bird species have been shown to have co-evolved with a particular species of Isospora. Disease can range from subclinical to severe and fatal, making infection and transmission of this parasite a concern for birds under managed care, particularly in institutions housing endangered species for breeding and reintroduction purposes. Whether birds in mixed-species enclosures represent a risk factor for severe isosporiasis due to infection with non-host-adapted strains is of concern for institutions managing these populations. To begin answering this question, we sought to characterize the host-specificity of Isospora species in a large number of passerine birds via retrospective sequencing of mitochondrial gene cytochrome oxidase (COI). Despite outliers, Isospora sequences largely grouped by host species and/or host family. Additional research is warranted into the degree of interspecies transmission and host-switching of Isospora parasites, and risk factors for the development of severe disease in passerine birds.